Sinergi sistem informasi akuntansi dan kecerdasan buatan dalam mendukung transformasi digital UMKM: Sinergi sistem informasi akuntansi dan kecerdasan buatan dalam mendukung transformasi digital UMKM - Octavia, Sandra Gadis (Maliki Interdisciplinary Journal, 2025)
Digital transformation in the era of Industry 4.0 demands that MSMEs adopt advanced technologies to enhance efficiency and competitiveness. The synergy between Accounting Information Systems (AIS) and Artificial Intelligence (AI) is key to supporting adaptive and data-driven financial decision-making. This article analyzes how the integration of AIS and AI can accelerate the processes of financial recording, analysis, and reporting, while also identifying the challenges faced by MSMEs in its implementation. A literature review reveals that accounting digitalization supported by AI improves accuracy, efficiency, and responsiveness in decision-making. However, it requires data security strategies, workforce training, and regulatory adjustments to ensure optimal benefits.